2023
DOI: 10.5709/acp-0376-4
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental and Beneficial Effects in Ongoing and Lasting Collaborative Memory: Insight From the Emotional Timeout Procedure

Abstract: Existing collaborative memory research has shown statistically significant detrimental and beneficial effects (i.e., collaborative inhibition, error pruning, and post-collaborative memory benefit). However, it remains unknown yet whether they are modulated by stimulus emotionality of adjacent stimuli and whether they would differ in distinct memory tasks (item memory vs. source memory). To address these issues, the current study adopted the emotional timeout procedure, where participants individually studied a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…By contrast, some other investigators (Barber et al, 2017;Choi et al, 2017;Ke et al, 2017;Nie & Deng, 2023) focused on various emotional situations, but they found mixed evidence of the detrimental effect of collaborative inhibition from different kinds of emotional valences. Ke et al (2017, Experiment 1) found stronger evidence of the amplitude of collaborative inhibition for recalling emotional words (including positive and negative) vs. neutral words; while there was no relative difference in the recall of positive and negative emotional words.…”
Section: Other Factors Influencing Collaborative Memory -Emotional Va...mentioning
confidence: 89%
See 4 more Smart Citations
“…By contrast, some other investigators (Barber et al, 2017;Choi et al, 2017;Ke et al, 2017;Nie & Deng, 2023) focused on various emotional situations, but they found mixed evidence of the detrimental effect of collaborative inhibition from different kinds of emotional valences. Ke et al (2017, Experiment 1) found stronger evidence of the amplitude of collaborative inhibition for recalling emotional words (including positive and negative) vs. neutral words; while there was no relative difference in the recall of positive and negative emotional words.…”
Section: Other Factors Influencing Collaborative Memory -Emotional Va...mentioning
confidence: 89%
“…Collaborative memory is operationally defined as the memory for experiences previously encountered individually or collaboratively but retrieved collaboratively (Abel & Bäuml, 2020;Browning et al, 2018;Choi et al, 2017;Ke et al, 2017;Maswood et al, 2019;Nie et al, 2019Nie et al, , 2022Nie et al, , 2021bNumbers et al, 2014). Information learned in collaboration can be incorporated into a partner's memory and is also subject to reconstruction, elaboration, or even distortion (Bays et al, 2017;Hinds & Payne, 2018;Maswood et al, 2021;Nie & Deng, 2023;Nie et al, 2019Nie et al, , 2022Nie et al, , 2021b.…”
Section: Collaborative Memorymentioning
confidence: 99%
See 3 more Smart Citations